Pentingnya Komunikasi Efektif dalam Pendidikan bagi Anak Usia Dini - Tio Rosalinda S. Pakpahan; Jumra Fadila; Henni Sara Gracia Br Ginting (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Effective communication between teachers and young children is a key factor in supporting the learning process and holistic development of children. This research aims to identify the most effective communication strategies in the context of early childhood education and understand their impact on children's learning engagement and achievement. This research is a qualitative approach with in-depth interviews, classroom observations, and documentation analysis. This research was carried out at An Nizam Islamic School Kindergarten Jl. Tuba II No 62, Tegal Sari Mandala III, Kec. Medan Denai, Medan City, North Sumatra 20226. The subjects in this research were PGPAUD STUDENTS and the role of effective communication in education for early childhood. The research results show that the use of two-way communication, nonverbal communication techniques, and an inclusive communicative approach significantly increases children's active participation and emotional involvement in teaching and learning activities. In addition, this research found that positive and supportive communication from teachers contributed to increasing children's self-confidence and independence.